Bolezni srca pri starostnikih - pristop k bolniku in splošni ukrepi - Horvat, Matija (Zdravniški vestnik, 2008)
Frequent mistakes in diagnostic and therapeutic approach toward patients over age 65 years are observed. History and basic clinical examination are often too superficial. The importance of some laboratory findings are frequently overestimated. The entire diagnostic procedure in old patient takes probably three to five times more than in average middle age person. In general, non-pharmacological principles in the treatment of the heart diseases are emphasized, especially interval aerobic training in heart failure patients.
Keywords: Adverse Effects; Aged; Anamneza; Diagnosis; diagnostika; Drug Therapy; Exercise; Fizikalna preiskava; Heart Diseases; Ischemic Preconditioning, Myocardial; Ishemična, predstopnja miokardna; kardiologija; Medical History Taking; Physical Examination; Srce, bolezni; Starostniki; Telesna vadba; Therapy; zdravljenje; Zdravljenje z zdravili